Dengue: a clinical & hematological study - Dr. Evelyn Angel S; Dr. Sivasankaran M; Dr. Elizabeth Chacko (Tropical Journal of Pathology and Microbiology, 2017)
Introduction: Dengue has positioned itself as the most important mosquito borne viral disease in the world. Current estimates report that at least 112 countries are endemic for Dengue and around 40% of the world populations are at risk in tropics and subtropics.Objective: The objective of this study is to analyze the hematological findings in dengue illness and to correlate the same with the clinical course.Materials and Methods: The present study was conducted in the Department of Pathology, Sree Mookambika Institute of Medical Sciences, Kulasekharam, Kanyakumari District, Tamilnadu during a period of three years from 2013 to 2015, where fifty dengue positive cases were analyzed from the Department of General Medicine.Results: A history of fever with retroorbital pain, myalgia and headache was noted in 7(14%), 43(86%) and 50 (100%) of the cases respectively. Of the cases studied, only one (2%) of the patients had a major bleeding manifestation, whereas minor bleeding manifestations were noted in 8 (16%) of the cases. Thrombocytopenia was noted 48 patients. Leukopenia was observed in 22 (73%), while leukopenia with reversal of neutrophil lymphocyte ratio was observed in 6(20%) of the patients. A rising haematocrit was noted in (16%) of the cases.Conclusion: It was concluded in this study that fever in the presence of thrombocytopenia, leukopenia, reversal of neutrophil lymphocyte ratio and a rising haematocrit should raise a strong suspicion of Dengue fever for which confirmation must be done. Thrombocytopenia was found to be an important prognostic indicator during hospital stay and/or follow up.